Integrated series/parallel connection for photovoltaic laser power converters with optimized current matching. (19th October 2020) - Wagner, Lukas; Reichmuth, Sebastian Kasimir; Philipps, Simon P.; Oliva, Eduard; Bett, Andreas W.; Helmers, Henning
Abstract: In this paper, we present a stepped architecture optimized for current matching in high‐voltage laser power converter photovoltaic (PV) cells. The integrated series/parallel connection in stepped PV cells combines the advantages of well‐known multijunction and multisegment approaches with respect to current matching, whereas their specific drawbacks are circumvented. The superior misalignment tolerance of stepped PV cells in comparison with multisegment cells is shown by simulations of the maximum acceptable misalignment ( MAM ) for a range of devices with various output voltages. We present the first realization of stepped PV cells with two stacked GaAs‐based pn‐junctions. Thereby, the unique properties of the lateral current flow in the bottom cell and the assessment of the optical absorption in the subcells are discussed. Moreover, the effects of segmentation and number of stacked junctions on the I‐V characteristics are investigated. Finally, the behavior towards misalignment of a laser spot is studied for stepped and multisegment PV cells. An optimal current matching for misalignment‐prone power‐by‐light systems is found with a six‐segment stepped PV cell. Abstract : A stepped architecture optimized for current matching in high‐voltage laser power converter photovoltaic (PV) cells is presented. The integrated series/parallel connection in stepped PV cells combines the advantages of well‐known multi‐junction and multi‐segment approaches. The first realization of such devices is presented, assessing the effects of segmentation and number of stacked junctions on the I‐V characteristics as well as the behavior towards misalignment of a laser spot.